Kawin Hamil Dan Implikasinya Terhadap Hak Keperdataan Anak Zina Menurut Khi, Hukum Positif Dan Hukum Islam - Armaya Azmi (Balai Diklat Keagamaan Medan, 2021)
Pregnant marriage due to adultery has consequences that have an impact on the validity of marriage and the civil status of the child born. The discourse on pregnant marriage and adultery continues to be a never-ending conversation. Is it permissible for a man to marry a woman who is pregnant? How about the civil rights of children who are born? On whom was the lineage leaned? Is he entitled to inherit his mother's father's property? Does the husband of the mother have the right to be the guardian of marriage? Different perspectives cause differences in addressing the problem of pregnant marriage and adultery. This study seeks to reveal the problem of pregnant marriage and its implications for children born, from the perspective of the Compilation of Islamic Law as a product of Indonesian jurisprudence, also looking at positive law and studying it in the perspective of Islamic law, then providing analysis and comparisons from these various points of view.